PERBANDINGAN PERILAKU SEHARI-HARI KUCING RAS (HIMALAYAN) DAN KUCING LOKAL (DOMESTIK/RUMAHAN) (FELIS CATUS) - Marta, Fadhillah; Nugroho, Anwari Adi; Pangestu, Prestiani Yulia; Armania, Vallery; Ardiansyah, Muhammad Ilham; Yoshia, Selumiel (FKIP Universitas Tanjungpura, 2026)
This study aims to explore and compare the daily behavioral patterns of purebred Himalayan cats and domestic (corner) cats (Felis catus) within a shared environmental context. Observations were carried out in Kesongo Hamlet, Sukoharjo Regency, employing scan sampling and ad libitum techniques over a three-week period. Recorded behaviors were classified into affiliative, self-maintenance, and negative categories. The findings revealed that Himalayan cats demonstrated a higher frequency of affiliative behaviors, including feeding, autogrooming, and approaching humans indicating a predisposition to emotional bonding and a preference for stable domestic settings. Conversely, domestic cats primarily exhibited self-maintenance behaviors such as roaming and climbing, reflecting stronger adaptive traits and instinctual responses to dynamic environments. Negative behaviors were relatively rare in both groups; however, aggressive tendencies were more commonly observed in domestic cats. These results underscore the influence of both genetic predispositions and environmental conditions in shaping feline behavior. The study offers valuable contributions to the field of ethology and provides practical insights for enhancing feline welfare by addressing breed-specific behavioral needs.